2017
DOI: 10.1002/1878-0261.12134
|View full text |Cite
|
Sign up to set email alerts
|

Tissue glycomics distinguish tumour sites in women with advanced serous adenocarcinoma

Abstract: In the era of precision medicine, the tailoring of cancer treatment is increasingly important as we transition from organ‐based diagnosis towards a more comprehensive and patient‐centric molecular diagnosis. This is particularly the case for high‐grade serous adenocarcinomas of the ovary and peritoneum, which are commonly diagnosed at an advanced stage, and collectively treated and managed similarly. We characterized the N‐ and O‐glycome of serous ovarian (OC) and peritoneal cancer (PC) tissues using PGC‐LC‐ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
(86 reference statements)
2
19
0
Order By: Relevance
“…Sialylated N‐ glycan structures have previously been found to be glyco‐markers of tumorigenesis . (Hex) 2 (HexNAc) 2 (NeuAc) 1 + (Man) 3 (GlcNAc) 2 was discovered in our study to be predominantly in late‐stage OC relative to the early‐stage patients (Figure , Supporting Information).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Sialylated N‐ glycan structures have previously been found to be glyco‐markers of tumorigenesis . (Hex) 2 (HexNAc) 2 (NeuAc) 1 + (Man) 3 (GlcNAc) 2 was discovered in our study to be predominantly in late‐stage OC relative to the early‐stage patients (Figure , Supporting Information).…”
Section: Discussionmentioning
confidence: 53%
“…isolated N‐ glycans from FF endometrioid, serous, and healthy OC tissue sections and discovered that bisecting N‐ glycan structures were elevated in the serous OC tissue as well as the glycosyltransferase enzyme, MGAT 3. More recently, the glycomes from cancer tissue originating from the ovaries and peritoneum were compared using PGC‐LC‐ESI‐MS/MS . This study reported high levels of α‐2‐6 sialylated and bisecting N‐ glycan structures from both cancers originating from the ovaries and peritoneum.…”
Section: Introductionmentioning
confidence: 94%
“…H5N5F1) (51), and potentially also Lac-diNAc (e.g. H3N6F1) (51). The proposed monosaccharide compositions were further validated with both MS/MS fragmentation analysis and exoglycosidase digestions.…”
Section: Discussionmentioning
confidence: 91%
“…H3N4F1) (21), bisecting GlcNAc (e.g. H5N5F1) (51), and potentially also Lac-diNAc (e.g. H3N6F1) (51).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation into the N‐ glycome of women with advanced serous adenocarcinoma identified α 2–6 sialylated structures in both OC and peritoneal cancer, with the majority displaying bi‐antennary mono‐ and di‐sialylation as well as bisecting . PGC–LC–ESI–MS/MS revealed that LacdiNAc motifs were unique to serous OC only and correlated with the elevated gene expression of the glycosyltransferases, B4GALNT3 and B4GALNT4, in patients.…”
Section: The Ovarian Cancer N‐glycome Characterised Using Mass Spectrmentioning
confidence: 99%